Perception of the quality of life of individuals with DCNT during the period of social isolation (Research, Society and Development, 2021)
The study aimed to evaluate the perception of the quality of life of individuals with CNCDs during the period of social isolation, therefore, it is an observational, cross-sectional study, with a sample of 17 individuals, where the participants took the Quality of Life Questionnaire. Vida SF-36, as well as a Nutritional Anamnesis, to collect data about the population, and a 24-Hour Recall, to show the sample's dietary consumption. The study was approved by the Research Ethics Committee. From the evaluation of the SF-36 questionnaire, it was possible to observe that none of the domains had a higher average score, characterizing a low to medium quality of life, mainly highlighting the Pain and Limitations due to Emotional Aspects domains, showing the fragility generated by social isolation and the adaptations that were made, leading to losses in other domains such as Vitality, General Health and Mental Health, that being said, the social isolation carried out due to the Covid-19 pandemic proved to be a major factor in worsening the quality of life of individuals with NCDs, the most affected population, as it fits as a risk group.